1976
DOI: 10.1111/j.1365-2125.1976.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

beta‐Adrenoceptor blocking activity and duration of action of pindolol and propranolol in healthy volunteers.

Abstract: The beta‐adrenoceptor blocking activities of pindolol and propranolol have been investigated in healthy male volunteers. Pindolol was about forty times more potent than propranolol in reducing isoprenaline‐ induced tachycardia. Pindolol (5 mg) and propranolol (u99 mg) were approximately equiactive in reducing exercise‐induced tachycardia, 2 h after oral administration. The duration of action of pindolol is significantly longer than that of propranolol; 24 h after pindolol (kmg), 36+/‐5% of the masimum effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
1

Year Published

1977
1977
1990
1990

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 11 publications
9
34
1
Order By: Relevance
“…Higher starting doses were used after administration of the ,-adrenoceptor blocking drugs. From the isoprenaline dose-response curves the dose of isoprenaline required to increase heart rate to 120 beats/min was determined, as described previously (Aellig, 1976). Dose-response relationship of oral doses from 0.5 to 10 mg in comparison with 5 and 15 mg pindolol on exercise-induced tachycardia Six volunteers with a mean age of 27 + 1 years and a mean body weight of 75 ± 4 kg received oral doses of 0.5 and 2 mg of bopindolol and 5 and 15 mg of pindolol in randomised order.…”
Section: Methodsmentioning
confidence: 99%
“…Higher starting doses were used after administration of the ,-adrenoceptor blocking drugs. From the isoprenaline dose-response curves the dose of isoprenaline required to increase heart rate to 120 beats/min was determined, as described previously (Aellig, 1976). Dose-response relationship of oral doses from 0.5 to 10 mg in comparison with 5 and 15 mg pindolol on exercise-induced tachycardia Six volunteers with a mean age of 27 + 1 years and a mean body weight of 75 ± 4 kg received oral doses of 0.5 and 2 mg of bopindolol and 5 and 15 mg of pindolol in randomised order.…”
Section: Methodsmentioning
confidence: 99%
“…This formula can be applied when intravenous data are not available and when the drug is eliminated mainly by metabolism as in the case of oxprenolol (Riess et al, 1975). Since pindolol (LB 46, Viskeng), a P-adrenoceptor blocking agent (Aellig, 1976a), is metabolized in man to only a moderate extent and is mainly excreted unchanged in the urine (Gugler, Herold & Dengler, 1974), it was of interest to review published and unpublished pharmacokinetic data on this compound in order to ascertain whether or not it is subject to an appreciable first-pass effect.…”
Section: Pindolol Ap-adrenoceptor Blocking Agent With a Negligible Fmentioning
confidence: 99%
“…Although observations in patients with hypertension have shown that satisfactory control of arterial pressure can be obtained throughout a 24 h period with twice daily administration (Berglund, Anderson, Habssen & Olander, 1973) and even once daily administration of propranolol (Wilson, Morgan & Morgan, 1976;Douglas-Jones, Baber & Lee, 1978), this may not be an effective regime for other 0306-5251/80/010033-08 $01.00 conditions such as angina or cardiac arrhythmias where the therapeutic effect may be more directly related to cardiac JJ-adrenoceptor blockade which is not maintained over 24 h after single dose of 100 mg propranolol (Aellig, 1976). Although a therapeutic effect with propranolol may be obtained in hypertension by giving the total daily amount as a single dose once per day, high plasma levels will occur shortly after administration which may produce adverse effects.…”
Section: Introductionmentioning
confidence: 99%